Ted - DiTerlizzi, Tony. (New York Aladdin Paperbacks, 2004)
A young boy manages to get his busy father's attention with the help of a special imaginary friend.
Originally published in 2001.
Keywords: Imaginary playmates -- Fiction; Fathers and sons -- Fiction